2018
DOI: 10.1103/physrevaccelbeams.21.064701
|View full text |Cite
|
Sign up to set email alerts
|

Linac booster for high energy proton therapy and imaging

Abstract: For an optimal exploitation of the benefits of proton therapy the most accurate dose delivery system should be used. The TERA Foundation has extensive experience in the field of high gradient high frequency linacs. This paper describes a particular design of a 3 GHz linac boosting the typical cyclotron beams for proton therapy of 230-250 MeV up to 350 MeV. Such an upgrade of a typical proton therapy facility enables performing proton radiography, as well as extending therapeutic capabilities with high energy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Alternative solutions to cyclotrons and synchrotrons have been investigated, all pointing at lower cost and more compact designs. Linac-based designs are being investigated since more than a decade [42]. A compact and modular design has been developed by AVO-ADAM (Advanced Oncotherapy -Application of Detectors and Accelerators to Medicine, Geneva, Switzerland), that is currently being installed and commissioned.…”
Section: Other Technologiesmentioning
confidence: 99%
“…Alternative solutions to cyclotrons and synchrotrons have been investigated, all pointing at lower cost and more compact designs. Linac-based designs are being investigated since more than a decade [42]. A compact and modular design has been developed by AVO-ADAM (Advanced Oncotherapy -Application of Detectors and Accelerators to Medicine, Geneva, Switzerland), that is currently being installed and commissioned.…”
Section: Other Technologiesmentioning
confidence: 99%
“…A LInac BOoster (LIBO) CCL structure has already been designed and tested 68,69 . LIBOs have also been considered to boost the energy of a cyclotron‐based proton therapy system for proton imaging 70,71 …”
Section: Linear Uhdr Acceleratorsmentioning
confidence: 99%
“…While the maximum beam energies at SNAKE (currently 20 MeV, 70 MeV with a proposed update (101)) are sufficient for preclinical applications, magnetically focused minibeams with clinical energies may be achieved with a recently proposed nozzle concept design (96). A design study evaluating this nozzle in combination with the proton linac LIGHT (102) found that proton minibeams with widths between 0.6 and 0.9 mm FWHM and energies up to 200 MeV could be delivered at Bragg peak dose rates of ∼ 50-1500 Gy/s (97). This could enable the study of proton FLASH-MBRT but also FLASH-GRID-RT in both experimental and, more importantly, clinical contexts.…”
Section: Protons and Ionsmentioning
confidence: 99%